2011
DOI: 10.1111/j.1556-4029.2011.01977.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Tool Mark Analysis of Cut Costal Cartilage*,†

Abstract: This study was designed to establish the potential error rate associated with the generally accepted method of tool mark analysis of cut marks in costal cartilage. Three knives with different blade types were used to make experimental cut marks in costal cartilage of pigs. Each cut surface was cast, and each cast was examined by three analysts working independently. The presence of striations, regularity of striations, and presence of a primary and secondary striation pattern were recorded for each cast. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In the study of cartilage stab injuries, Pounder et al [13][14][15] also made an important contribution, demonstrating that striation marks left by serrated knives might enable the identification of a class characteristic of serrated blades. Love et al [16] confirmed the results provided by the study of Pounder et al but also demonstrated that a blade type classification may lead to high misclassification rates. Two further studies performed by Pounder et al [17,18] on soft tissues showed that the identification of a stab injury may be easier when the stabbing tool is held perpendicular to the wounded tissue.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the study of cartilage stab injuries, Pounder et al [13][14][15] also made an important contribution, demonstrating that striation marks left by serrated knives might enable the identification of a class characteristic of serrated blades. Love et al [16] confirmed the results provided by the study of Pounder et al but also demonstrated that a blade type classification may lead to high misclassification rates. Two further studies performed by Pounder et al [17,18] on soft tissues showed that the identification of a stab injury may be easier when the stabbing tool is held perpendicular to the wounded tissue.…”
Section: Introductionmentioning
confidence: 50%
“…Costal cartilage can be very important in real case scenarios as it is injured in many cases of stab wounds to the chest. Previous studies demonstrated that characteristic cut marks may also be detected on cartilage, especially when serrated-edged blades are used, thereby providing crucial aid in the identification of the wounding weapon [12][13][14][15][16]. At the moment, however, the microscopic differences between cut marks and blunt force fractures on cartilage, along with the modifications they undergo when decomposition occurs, have never been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 95%
“…Three doctoral level anthropologists examined each specimen independently. Each analyst has a minimum of 6 years of experience analyzing tool marks in bone and cartilage and previously participated in a knife cut mark validation study . To ensure that each analyst understood the variables, a pilot study of 10 saw marks was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on cut marks have involved the use of qualitative description of the features of bone surface disruption, using either light microscopy or Scanning Electron Microscopy (SEM) (Bromage and Boyde, 1984;Greenfield, 1999;West and Louys, 2007;Love et al, 2012). Recently, authors have begun to look at quantitative analysis (Bello and Soligo, 2008;Bello et al, 2009) and the use of three dimensional microscopy (Boschin and Crezzini, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine ribs were chosen as they are a commonly selected species for this type of study (Croft and Ferllini, 2007;Kooi and Fairgrieve, 2012;Love et al, 2012). There was no disruption of the overlying soft tissue in the central areas of the ribs to be used, therefore no pre-existing cut marks from the processing of the meat.…”
Section: Materials and Methods Experimental Cut Marksmentioning
confidence: 99%